Professional development opportunities for in-company trainers : a compilation of good practices - (:unkn) unknown (Publications Office of the European Union, 2010)
"The aim of the present study was to shed light to existing initiatives promoting the professional development of in-company trainers. As a first step, the study focused on a review of existing literature relevant to the professional development of in-company trainers. The desk research confirmed that there is a very limited pool of literature throughout Europe focusing on in-company trainers. As a second step, 13 case studies of initiatives promoting the professional development of in-company trainers were carried out between February and May 2009. The selection of case studies includes examples of: establishing regulation and standardisation measures for trainers; developing registers of training practitioners and other forms of quality assurance certifications; validating and recognising non-formal and informal learning of trainers; encouraging continuous training for in-company trainers; supporting trainers through online resources; creating networks of trainers and communities of practice." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; I 2.2.1 Westeuropa; I 2.1 Deutschland; Bildungspersonal; Ausbilder; Ausbildende Fachkraft; Professionalisierung; Fallstudie; Irland; Zypern; Finnland; Österreich; Frankreich; Tschechische Republik; Malta; Norwegen; Dänemark; Bundesrepublik Deutschland; Italien; Vereinigtes Königreich; Belgien